African Baobabs with False Inner Cavities: The Radiocarbon Investigation of the Lebombo Eco Trail Baobab - Patrut, Adrian; Woodborne, Stephan; von Reden, Karl F.; Hall, Grant; Hofmeyr, Michele; Lowy, Daniel A.; Patrut, Roxana T. (PLoS One, 2015)
The article reports the radiocarbon investigation results of the Lebombo Eco Trail tree, a representative African baobab from Mozambique. Several wood samples collected from the large inner cavity and from the outer part of the tree were investigated by AMS radiocarbon dating. According to dating results, the age values of all samples increase from the sampling point with the distance into the wood. For samples collected from the cavity walls, the increase of age values with the distance into the wood (up to a point of maximum age) represents a major anomaly. The only realistic explanation for this anomaly is that such inner cavities are, in fact, natural empty spaces between several fused stems disposed in a ring-shaped structure. We named them false cavities. Several important differences between normal cavities and false cavities are presented. Eventually, we dated other African baobabs with false inner cavities. We found that this new architecture enables baobabs to reach large sizes and old ages. The radiocarbon date of the oldest sample was 1425 +/- 24 BP, which corresponds to a calibrated age of 1355 +/- 15 yr. The dating results also show that the Lebombo baobab consists of five fused stems, with ages between 900 and 1400 years; these five stems build the complete ring. The ring and the false cavity closed 800-900 years ago. The results also indicate that the stems stopped growing toward the false cavity over the past 500 years.
PT: J; TC: 0; UT: WOS:000348470400021